Scalar-gauge dynamics in (2+1) dimensions at small and large scalar couplings - Philipsen, O; Teper, M; Wittig, H (1998)
We present the results of a detailed calculation of the excitation spectrum of states with quantum numbers JPC = 0++, 1- and 2++ in the three-dimensional SU(2) Higgs model at two values of the scalar self-coupling and for fixed gauge coupling. We study the properties of Polyakov loop operators, which serve to test the confining properties of the model in the symmetric phase. At both values of the scalar coupling we obtain masses of bound states consisting entirely of gauge degrees of freedom (glueballs), which are very close to those obtained in the pure gauge theory. We conclude that the previously observed, approximate decoupling of the scalar and gauge sectors of the theory persists at large scalar couplings. We study the crossover region at large scalar coupling and present a scenario how the confining properties of the model in the symmetric phase are lost inside the crossover by means of flux tube decay. We conclude that the underlying dynamics responsible for the observed dense spectrum of states in the Higgs region at large couplings must be different from that in the symmetric phase. © 1998 Elsevier Science B.V.